An Improved Algorithm of the Collision Detection Based on OBB - Chaoyang, Geng; Fenli, Gao (International journal of advanced network, monitoring, and controls, 2018)
Collision detection plays a vital role in improving the sense of immersion and realism in virtual environment. The bounding box is the most basic collision detection algorithm, The OBB intersect test tightness and can able to significantly reduce the number of bounding volume. and try to occupy less storage space. Propose a bounding box of direction cylindrical So it can be improved though surrounded objects more close, then improve the efficiency of collision detection.